Little Oxford Dictionary of Proverbs - Edited by Knowles, Elizabeth (New York Oxford University Press, 2009)
Featuring over 2,000 proverbs and sayings, both quirky and wise, on 250 different themes, the Little Oxford Dictionary of Proverbs draws on the latest Oxford Dictionaries research and ensures you can find a pithy saying for any occasion.
Include Index
Keywords: Proverbs, English